Neoadjuvant chemoradiotherapy followed by esophagectomy does not increase morbidity in patients over 70. Issue 5 (23rd August 2012) - Blom, R. L. G. M.; van, M.; Klinkenbijl, J. H. G.; Bergman, J. J. G. H. M.; Wilmink, J. W.; Richel, D. J.; Hulshof, M. C. C. M.; Reitsma, J. B.; Busch, O. R. C.; van, M. I.
Summary Esophagectomy in elderly esophageal carcinoma patients is correlated with a high morbidity and even mortality. Studies on neoadjuvant chemoradiotherapy (NT) in elderly patients are scarce. The aim of this study was to evaluate the effect of advanced age in combination with NT in esophageal carcinoma patients who underwent an esophagectomy. Patients who underwent NT prior to esophagectomy between 1993 and 2010 were divided into three groups: <70, 70–74, and ≥75 years. Toxicity of NT and postoperative morbidity were compared between groups. Primary endpoints were toxicity, complication rate, and survival. Two hundred thirteen patients underwent NT during the study period, 26 were aged 70–74 years, and 17 were ≥70 years. Toxicity of NT was comparable for younger and elderly patients (46% vs. 54% vs. 47%, P = 0.263). Overall complications occurred in 62% of younger patients versus 73% and 71% among patients aged 70–74 years and ≥75 years, respectively (P = 0.836). Cardiac complications occurred in 14% of younger patients versus 27% and 41% of elderly patients (P = 0.021). Three‐year survival rates were 59% versus 44% versus 31% among patients aged <70, 70–74, and ≥75 years, respectively (P = 0.237). Higher age (odds ratio 1.750, P < 0.001) was an independent risk factor for development of cardiac complications. Toxicity of NT and postoperative complications are comparable for patients aged <70, 70–74, and ≥75 years, with the exception of cardiac complications. Therefore, we consider NT followed by esophagectomy in elderly patients a safe treatment modality in our center.